Analyses of rain fade countermeasure technique time diversity at 26 GHz - Ismail, Ahmad Fadzil; Din, Jafri; Tharek , Abdul Rahman; Islam, Md. Rafiqul; Abdullah, Khaizuran (2012)
Measurements of 26 GHz attenuation due to rain were acquired from a microwave link set-up in Malaysia, a country in one of the most extreme weather with regard to rainfall rates. The data were analyzed with particular interest assessing the performance of Time Diversity as a conceivable fade mitigation technique in broadcast applications. The technique entails a process of retransmission of signals to obtain the required signal gain for improved output signal. An empirical relationship is proposed, enabling Time Diversity gain at mentioned frequency to be determined as a function of delay